Combined administration of FVIII and rFVIIa improves haemostasis in haemophilia A patients with high‐responding inhibitors – a thrombin generation‐guided pilot study. (10th May 2013) - Livnat, T.; Martinowitz, U.; Azar‐Avivi, S.; Zivelin, A.; Brutman‐Barazani, T.; Lubetsky, A.; Kenet, G.
Summary: Treatment of haemophilia A patients with inhibitors is challenging, and may require individually tailored regimens. Whereas low titre inhibitor patients may respond to high doses of factor VIII (FVIII), high‐responding inhibitor patients render replacement therapy ineffective and often require application of bypassing agents. Thrombin generation (TG) assays may be used to monitor haemostasis and/or predict patients' response to bypass agents. In this study we defined by TG, the potential contribution of FVIII to recombinant activated factor VII (rFVIIa)‐induced haemostasis in inhibitor plasma. Based upon results, prospectively designed individual regimens of coadministration of rFVIIa and FVIII were applied. Plasma samples from 14 haemophilia patients with inhibitors (including high titre inhibitors) were tested. The response to increasing concentrations of FVIII, rFVIIa or both was assayed by TG. Eight patients, chosen following consent and at physician's discretion, comprised the combined FVIII–rFVIIa therapy clinical study cohort. Combined spiking with FVIII/rFVIIa improved TG induced by rFVIIa alone in all inhibitor plasmas. Combined rFVIIa and FVIII therapy was applied during bleeding or immune tolerance to eight patients, for a total of 393 episodes. Following a single combined dose, 90% haemostasis was documented and neither thrombosis nor any complications evolved. During study period decline of inhibitor levels and bleeding frequency were noted. Pre‐analytical studies enabled us to prospectively tailor individual therapy regimens. We confirmed for the first time that the in vitro advantage of combining FVIII and rFVIIa, indeed accounts for improved haemostasis and may safely be applied to inhibitor patients.